The coverage of industrial action by the Mail & Guardian, 1999-2004 - Radebe, Mandla Joshua (My University, 2011)
The focus of this study is on the coverage of industrial action by the Mail & Guardian between 1999 and 2004. Mainly, the study seeks to understand the coverage of labour issues by the newspaper in post-apartheid South Africa. It is argued that the coverage, or lack of coverage, of labour issues by the paper is related to socio-economic and political conditions in the country. Literature on the influential role the ownership and control of media play in the content of news, as well as the influence of advertising, is analysed to attain a clear understanding of the pattern of coverage of labour news in post-apartheid South Africa. Therefore, the study uses the coverage of industrial action as a yardstick to measure as well as to understand the extent and the shift in editorial content of the newspaper with specific reference to industrial action. The main argument of the study is that the prevailing socio-economic and political conditions in South Africa, brought about by the advent of democracy, coupled with structural limitations play a fundamental role in determining the manner in which working-class issues are currently covered by the Mail & Guardian. It emerges in the study that the manner in which labour news in general and industrial action in particular are covered has shifted and thus replaced in the main by articles on labour politics. The extent to which the Mail & Guardian covers industrial action in the post-apartheid era has declined, and more emphasis is being placed on other beats that are not directly the interests of the poor and the working class.
M.A., Journalism and Media Studies, Faculty of Humanities, University of the Witwatersrand, 2006
Keywords: industrial action; press coverage; Mail & Guardian